Vote Influence in Group Decision-Making: The Changing Role of Justices' Peers on the Supreme Court - Maxwell R. Mindock; Glen R. Waddell (Institute of Labor Economics (IZA), 2019)
We consider the voting behavior of Supreme Court Justices, finding evidence of co-dependencies in their votes. Coincident with changes in the party imbalance of the Court over time, sharp discontinuities in these dependencies are evident. Overall, the patterns suggest a tradeoff between co-dependencies around political affiliations and individual ideologies, with more-equal party representation on the Court encouraging greater party awareness in Justice voting, and less-equal party representation allowing Justices across party lines but with similar ideologies to inform each other's votes.
Keywords: D7; K41; C21; 330; Supreme Court; voting; judicial behavior; spatial econometrics